Analysis of Interpersonal Communication to Improve Employee Performance at the Central Statistics Agency of Karawang - Rafly Agam Setyadi; Sungkono; Maman Mulya Karnama; Uus Mohammad Darul Fadli; Anim Zalina Azizan (Research in Management of Technology and Business, 2024)
This research aims to understand interpersonal communication at the Central Statistics Agency of Karawang. This study employs qualitative methods with a case study approach. Data collection techniques include observations, interviews, and documentation. The data analysis technique applies qualitative descriptive analysis. From the interview results, the author interprets the findings narratively, demonstrating that interpersonal communication plays a crucial role in enhancing employee performance. The findings show that interpersonal communication has an impact of up to 99.07% in improving employee performance. This study indicates that interpersonal communication can enhance employee performance by fostering a sense of comfort, building trust, and mutual assistance. Interpersonal communication among Central Statistics Agency of Karawang employees encompasses essential aspects such as openness, empathy, supportive attitudes, positive attitudes, and equality.